2011
DOI: 10.1021/ol200889s
|View full text |Cite
|
Sign up to set email alerts
|

Stelleralides A–C, Novel Potent Anti-HIV Daphnane-Type Diterpenoids from Stellera chamaejasme L.

Abstract: Three novel 1-alkyldaphnane-type diterpenes, stelleralides A–C (4–6), and five known compounds were isolated from the roots of Stellera chamaejasme L. The structures of 4–6 were elucidated by extensive spectroscopic analyses. Several isolated compounds showed potent anti-HIV activity. Compound 4 showed extremely potent anti-HIV activity (EC90 0.40 nM) with the lowest cytotoxicity (IC50 4.3 μM), and appears to be a promising compound for development into anti-AIDS clinical trial candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
76
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 24 publications
5
76
0
1
Order By: Relevance
“…As confirmed from the molecular formula, the 1 H and 13 C NMR revealed that the aliphatic chain of compounds 4 and 5 contained two more and four more methylene groups than mellerin B respectively. By detailed MS and NMR data analysis, compound 4 was identified as simplexin, a known compound previously isolated from the genus Pimelea (Thymelaeaceae) including P.simplex and P. elongata and other plant species (Asada et al, 2011;Hayes et al, 2010). Compound 5 was identified as montanin, from its MS and NMR data analysis and also in comparison with data from literature.…”
Section: Characterisation Of Compounds From the Stem Bark Extractmentioning
confidence: 90%
“…As confirmed from the molecular formula, the 1 H and 13 C NMR revealed that the aliphatic chain of compounds 4 and 5 contained two more and four more methylene groups than mellerin B respectively. By detailed MS and NMR data analysis, compound 4 was identified as simplexin, a known compound previously isolated from the genus Pimelea (Thymelaeaceae) including P.simplex and P. elongata and other plant species (Asada et al, 2011;Hayes et al, 2010). Compound 5 was identified as montanin, from its MS and NMR data analysis and also in comparison with data from literature.…”
Section: Characterisation Of Compounds From the Stem Bark Extractmentioning
confidence: 90%
“…19 The purity of gnidimacrin (>98%) was confirmed by quantitative high-performance liquid chromatography photo-diode array (HPLC-PDA) analysis and 1 H NMR spectroscopic analysis. Prostratin, staurosporin, and enzastaurin were purchased from LC Laboratories, Woburn, MA.…”
Section: Methodsmentioning
confidence: 99%
“…11,19 In particular, certain daphnane and tigliane diterpenoids have shown extremely potent anti-HIV activity at low nanomolar concentrations with relatively low cytotoxicity. 7,10 However, these compounds are very difficult to synthesize because of their complex structure. Accordingly, further analysis of the plant material was conducted to acquire a significant quantity of several known, as well as new, anti-HIV diterpenoids from S. chamaejasme .…”
mentioning
confidence: 99%